Nye styringsformer og anerkendelseskamp - den vrede hjemmehjælper? - Hanne Marlene Dahl (The Royal Danish Library, 2010)
New forms of Governance and Struggles about Recognition – the angry Home Helper? Struggles about recognition of care have evolved during the last decade in Western Europe. In Denmark struggles can be found within the field of elderly care and publicly employed home helpers. This mobilization seems to be related to the prevalence of a new form of governance, New Public Manage- ment (NPM), and is investigated from a top-down and a bottom-up perspective. A discourse analysis of political-administrative texts show a NPM inspired discourse that si- lences the qualifications of home helpers and reproduces misrecognition of care. Focus group interviews show that home helpers employ three different strategies towards this form of governance: the sweet, caring by the book and the professional home helper.